2008
DOI: 10.5174/tutfd.2008.01139.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting To Participation In Population-based Mammography Screening

Abstract: Objectives: This study aims to investigate the demographic or risk factors affecting participation in a population-based breast screening with mammography program in a rural area of Turkey. Patients and Methods:This definitive epidemiological study was carried out between December 2002 and August 2003, in a town of Ankara. Of the 784 women, 710 were interviewed and 462 (58.9%) of them participated in the screening. A questionnaire was used for collecting data. Results: The mean age of the women was 50.7±10.0 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Similarly, in our study, the low knowledge level of mammography and low screening mammography (34.9%) was detected among PHW. Consistent with the present study, screening mammography was found to be low in the previous research [ 27 29 ]. It was lower than expected especially considering the fact that participants were HW [ 13 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, in our study, the low knowledge level of mammography and low screening mammography (34.9%) was detected among PHW. Consistent with the present study, screening mammography was found to be low in the previous research [ 27 29 ]. It was lower than expected especially considering the fact that participants were HW [ 13 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although there are no available statistics showing the percentage of women who have received screening mammograms in Turkey, the Organization for Economic Co-operation and Development (OECD) has reported that the mean screening rate of women in Turkey over the age of 50 years between 2000 and 2009 was 12.4 % [9]. According to the results of studies conducted in Turkey, the rate of women who have had at least one screening mammogram over various periods has varied widely: 12.5 % by Canbulat and Uzun [24], 65.9 % by Açıkgöz et al [25], and 82.4 % by Maral et al [26]. Though the screening rate in this study fell within the defined range, it was higher than the average for Turkey as stated by the OECD [9], which may be due to the study being conducted within the city and not including women from rural areas.…”
Section: Discussionmentioning
confidence: 96%
“…In this study age has positive effect on doing mammography in women who go for a mammography at least once. Whereas according to the studies in other countries age had negative effect; in a study conducted in Turkey, elder women had 1.1 fold greater risk of nonparticipation in mammography screening (31) and in Korean women, age had significantly contributed to the poor participation in breast cancer screening programs (32). One of the reason for this difference is related to the modeling strategy for analyzing data.…”
mentioning
confidence: 98%